The Use of a Commercial Textbook in English 1 Course at a University in South Korea - Adaninggar Septi Subekti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
This study investigated the use of a commercial textbook in English 1 Course at a university in South Korea seen from the framework of a sound curriculum development. Thus, the use of a commercial textbook was analysed and evaluated in relation to elements of curriculum development, such as needs analysis, learning aims, syllabus, methodology, and materials, as well as assessments. It was found that the use of the textbook drove what were taught in the whole course and thus practically “functioned” as its syllabus. However, it was found that the textbook could not facilitate learners to achieve all of the learning aims of English 1 course and it contributed to a disparity of learners' achievements across different classes. Furthermore, the reading assessment, derived from the textbook, was unable to assess learners’ achievements in all of the learning aims of English 1 course. Thus, it is suggested that teachers form informal workshop groups among teachers where they can share problems they face in class and possible solutions on how to address them in areas within their control. Based on the results of the study as well as the limitations, some recommendations for future studies are also presented.Keywords: commercial textbook, English 1 Course, curriculum, syllabus